Sumac : recipes and stories from Syria - Atassi, Anas (Murdoch Books, 2021)
Sumac is a deep red spice that adds a vibrant lift to all kinds of food, and is a prized ingredient in both traditional and contemporary Syrian cuisine. This book includes over 80 recipes inspired by Anas Atassi's family recipes and travels, as well as the stories, celebrations and memories of loved ones in Syria that inspired the recipes. It includes the wonderful Friday breakfasts he'd eat in his grandmother's garden, his mother's sfeeha, along with the falafel he now loves to make for his friends, along with many other mezze, salads, meats, vegetables, and desserts. Sumac is an evocative and inspiring food journey that offers a glimpse into Syrian food culture's deep historical roots, which through millennia of cultural traditions and neighbouring influences have been shared and shaped to perfection.